2022
DOI: 10.1007/s11033-021-07071-9
|View full text |Cite
|
Sign up to set email alerts
|

Mini review ATF4 and GRP78 as novel molecular targets in ER-Stress modulation for critical COVID-19 patients

Abstract: Coronavirus disease 2019 (COVID-19) is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and has resulted in more than 4.4 million deaths worldwide as of August 24, 2021. Viral infections such as SARS-CoV2 are associated with endoplasmic reticulum (ER) stress and also increased the level of reactive oxygen species. Activating transcription factor 4 (ATF4) is preferentially translated under integrated stress conditions and controls the genes involved in protein homeostasis, amino acid tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…In our study, no association was observed regarding GRP78 and ICU outcome. GRP78 is an essential chaperone protein involved in the unfolded protein response (UPR) and its expression is regulated by activating transcription factor 4, which is activated in stress situations where there is a risk of protein misfolding, such as oxidative stress, anoxia/hypoxia, acute inflammation and amino acid deprivation [ 16 ]. UPR consists of a decrease in protein synthesis and an enhanced capacity of endoplasmic reticulum protein folding, in order to maintain cellular homeostasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, no association was observed regarding GRP78 and ICU outcome. GRP78 is an essential chaperone protein involved in the unfolded protein response (UPR) and its expression is regulated by activating transcription factor 4, which is activated in stress situations where there is a risk of protein misfolding, such as oxidative stress, anoxia/hypoxia, acute inflammation and amino acid deprivation [ 16 ]. UPR consists of a decrease in protein synthesis and an enhanced capacity of endoplasmic reticulum protein folding, in order to maintain cellular homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…ERS has been described to be associated with organ failure in patients suffering from a systemic inflammation response during septic shock or cardiac surgery with cardiopulmonary bypass [ 12 , 13 ]. SARS-CoV-2 infection and replication within the host cell may compete with the normal folding process, and may be responsible for both GRP78 overexpression and an increased unfolded protein response [ 14 , 15 , 16 , 17 ]. However, there are currently no data describing the GRP78 level in COVID-19 ICU patients.…”
Section: Introductionmentioning
confidence: 99%
“…[98][99][100][101] Our observations deepen our understanding of allosteric communication in the Hsp70 system and how a ubiquitous but diverse protein class has adapted to different cellular environments and cochaperone interaction partners. As Hsp70 have also been suggested to be promising therapeutic factors in a range of contexts, among them neurodegenerative diseases 2,3,[7][8][9][10][11][12] and csBiP as a coreceptor of the pandemic SARS-CoV-2 virus, [40][41][42][43][44] investigating such evolutionary differences in further detail may become a key step in developing medical applications.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34] Tumors and cells under stress show elevated levels of csBiP compared to normal cells, which has prompted investigations into applications for cancer detection and therapy. [35][36][37][38][39] Moreover, csBiP is implicated as a coreceptor promoting host cell entry for several coronaviruses, including the pandemic virus SARS-CoV-2, [40][41][42][43][44] and has been suggested as a therapeutic factor for severe COVID-19 cases. 41,44 Elucidating the evolutionary differences distinguishing Hsp70 variants could deepen our understanding of this important protein class and help to tailor drugs to the specific properties of the targeted protein.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation